EARTHS GLACIAL RECORD AND ITS TECTONIC SETTING - Eyles N. (My University, 1993)
Glaciations have occurred episodically at different time intervals and for different durations in Earth's history. Ice covers have formed in a wide range of plate tectonic and structural settings but the bulk of Earth's glacial record can be shown to have been deposited and preserved in basins within extensional settings. In such basins, source area uplift and basin subsidence fulfill the tectonic preconditions for the initiation of glaciation and the accomodation and preservation of glaciclastic sediments. Tectonic setting, in particular subsidence rates, also dictates the type of glaciclastic facies and facies successions that are deposited. Many pre-Pleistocene glaciated basins commonly contain well-defined tectonostratigraphic successions recording the interplay of tectonics and sedimentation; traditional climatostratigraphic approaches involving interpretation in terms of either ice advance/retreat cycles or glacio-eustatic sea-level change require revision.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен